1999
DOI: 10.1211/0022357991772718
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Ciprofloxacin into the Central Nervous System in Rats with Acute Renal or Hepatic Failure

Abstract: Pharmacokinetic changes of various drugs have been reported in renal or hepatic failure. The present study employed ciprofloxacin, a quinolone antibiotic having neurotoxic side effects, to assess the influence of these diseases on distribution of ciprofloxacin into the central nervous system (CNS). After intravenous dosing of ciprofloxacin (10-30 mg kg(-1)), ciprofloxacin levels in plasma and brain were measured in normal rats (Wistar, male, 10-week-old) and those with acute renal and hepatic injuries which we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…This delay in the elimination of the drug may be the result of renal abnormalities caused by uranyl nitrate; this result agreed with [29], that observed the prolongation in the elimination half-life of ciprofloxacin in uranyl nitrate-treated rats when compared with those in the normal rats. A longer mean residence time (MRT) was found in renal damaged ducks as compared to healthy ones.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This delay in the elimination of the drug may be the result of renal abnormalities caused by uranyl nitrate; this result agreed with [29], that observed the prolongation in the elimination half-life of ciprofloxacin in uranyl nitrate-treated rats when compared with those in the normal rats. A longer mean residence time (MRT) was found in renal damaged ducks as compared to healthy ones.…”
Section: Discussionsupporting
confidence: 91%
“…Apparent differences were observed in pharmacokinetics parameters of ciprofloxacin between patients with severe impairment of renal function and those with normal renal function, AUC was increased, Cl was reduced, and t 1/2( β ) was prolonged in impaired renal function patients [31]. Also, in uranyl nitrate-treated rats, Cl was reduced compared with those in the normal rats [29]. …”
Section: Discussionmentioning
confidence: 99%
“…Thus, CCl 4 -treated rats are widely used as common pathological models of acute hepatic failure in pharmacokinetic experiments. [10][11][12][13][14][15][16][17][18] Marked elevation in the activities of ALT and AST was confirmed in CCl 4 -treated rats, indicating the development of liver injury. CCl 4 intoxication is involved in reducing hepatic blood flow as well as the activities of hepatic enzymes responsible for drug metabolism, 14,19) and it has been reported that the elimination clearance of many drugs that undergo hepatic removal is markedly reduced in CCl 4 -treated rats.…”
Section: Discussionmentioning
confidence: 86%
“…Acute hepatic failure induced experimentally with CCl 4 in animals is accompanied by a reduction in the renal tubular secretion of cefpiramine and impaired intestinal sugar transport, in addition to the suppression of various hepatic functions (Li et al 1990 ;Sugihara et al 1992 ;Castilla-Cortazar et al 1997). Acute renal failure induced by glycerol or uranyl nitrate also reduces the hepato-biliary transport of certain drugs, modulates the distribution of drugs into the central nervous system and decreases the activity of various hepatic microsomal enzymes (Bowmer & Yates 1984 ;Naora et al 1999). Thus, dysfunction of the liver or kidney, both important organs in the detoxification of xenobiotics, exerts a major influence on the pharmacokinetics of various drugs not only in the target organ but also in other organs.…”
Section: Introductionmentioning
confidence: 99%